2014
DOI: 10.1007/s10964-014-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Invited Address: “The Times They Are A-Changin’” Gene Expression, Neuroplasticity, and Developmental Research

Abstract: For good reason, social scientists have a long history of being suspicious of biological explanations of human behavior. Importantly, however, recent paradigmatic shifts in the life sciences have largely obviated these longstanding concerns. We highlight the changes that have occurred in genetics with its movement away from genetic determinism to an emphasis on epigenetics and in neuroscience with its switch from a fixed to a neuroplastic view of the brain. We describe these new developments noting the way the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
6
0
4
Order By: Relevance
“…In particular, studies conducted jointly by researchers from the practice fields and the science field have advanced our understanding of the biological basis for the designer's or artist's experiences (Goguen & Myin, 2000;Seitamaa-Hakkarainen, 2015;Seitamaa-Hakkarainen, Huotilainen, Mäkelä, Groth, & Hakkarainen, 2014;Varela et al, 2003;Zaidel, 2005). Similar results emerge from the fields of education or development studies, where such interdisciplinary perspectives have been found to support and expand previous research on complex human behaviors, development, or experiences (Ansari & De Smedt, 2012;De Smedt et al, 2011;Juelskjaer, Moser, & Schilhab, 2008;Simons & Klopack, 2015).…”
Section: Introductionsupporting
confidence: 84%
“…In particular, studies conducted jointly by researchers from the practice fields and the science field have advanced our understanding of the biological basis for the designer's or artist's experiences (Goguen & Myin, 2000;Seitamaa-Hakkarainen, 2015;Seitamaa-Hakkarainen, Huotilainen, Mäkelä, Groth, & Hakkarainen, 2014;Varela et al, 2003;Zaidel, 2005). Similar results emerge from the fields of education or development studies, where such interdisciplinary perspectives have been found to support and expand previous research on complex human behaviors, development, or experiences (Ansari & De Smedt, 2012;De Smedt et al, 2011;Juelskjaer, Moser, & Schilhab, 2008;Simons & Klopack, 2015).…”
Section: Introductionsupporting
confidence: 84%
“…Epigenetic factors such as methylation appear to be one important mechanism whereby life experiences become biologically embedded and can serve as the physiological underpinnings for cognitive, emotional, and behavioral traits tailored for adaptation to environmental demands (Landecker & Panofsky, 2013; Meloni, 2014; Simons & Klopack, 2015). Building on this idea, the current study investigated the extent to which individuals might adapt to environmental adversity by downregulating the OXTR gene.…”
Section: Discussionmentioning
confidence: 99%
“…This would reduce responsiveness to oxytocin, thereby fostering a cold, guarded orientation when interacting with others (supported biologically by increased cortisol production, greater activation of the amygdala, etc.). Such calibration of OXTR would be functional from an evolutionary perspective because it prepares the individual for a hostile, unpredictable environment where others are not trustworthy (Simons & Klopack, 2015). Cognitively, this orientation would be similar to the negative cognitive schemas that place a person at risk for depression.…”
Section: The Oxtr Genementioning
confidence: 99%
“…We have entered a ‘post‐genomics’ era, an expression widely used by geneticists themselves . While these developments might matter less for ‘monogenic’ inherited disorders such as Huntington's disease, they are clearly important for more complex disorders such as Type I diabetes .…”
Section: Resultsmentioning
confidence: 99%